A habilidade de inferir humor em tirinhas: o papel da mediação e da sistematização de atividades - Denis Pereira de Andrade (2016)
This work investigates effective teaching strategies to addres reading difficulties of the students of the 8th grade of elementary school in inferring the humor in the genre strip. The work is justified by proposing reflections on essential reading skills for understanding not only of the genre comic strip, but other genres too - the inference. Moreover, the work deepens the study on the effects of humor in a very gender used in textbooks - the strip - which attracts the attention of students-readers that do not always understand. It seeks to answer the following questions: "What is the contribution of mediation (teacher-student) to develop the ability to infer the humor in the genre comic strip?"; "To what extent the systematization of comic reading activities, as presented by textbooks 8th grade of elementary school, contributes to the development of the ability to infer humor?"; "What school activities are more efficient for the development of the ability to infer humor in comic strips?" The initial hypothesis of research is that the ability to infer the humor in comic strips can be developed with the proposition of teaching strategies - mediated and systematized by teacher. As a theoretical framework of this study, the research uses authors as Bakhtin ([1952/1953] 2003), Possenti (2005, 2013), Cafiero (2005), Dell'Isola (2001), Ramos (2007), Solé (1998) Vygotsky ([1984] 2007), among others. As a methodology, a collection of textbooks of English language teaching was analyzed in order to see how is the exploration of gender strip. From this analysis and diagnostic activities made by users of the collection focused workshops were developed in the development of the ability to infer mood in comic strips. After the workshops, the students made verification activities. Through comparisons between the results obtained by students in the diagnostic activity and the carried out after the development of the workshops, it was possible to verify the development of students' reading skills. The results show that the ability to infer the humor in comic strips is likely to be taught through systematically organized activities and developed in a manner mediated by the teacher. After the workshops, students demonstrated and understand the humor in comic strips - and explain that understanding - because they were stimulated through questions, to understand the elements (verbal and visual) that constitute the genre comic strip as well as the strategies used to production effect of humor in researching gender.